Reusable Floating Beads with Immobilized Xylose-Fermenting Yeast Cells for Simultaneous Saccharification and Fermentation of Lime-Pretreated Rice Straw - Guan, Di; Zhao, Rui; Li, Yuan; Sakakibara, Yoshikiyo; Ike, Masakazu; Tokuyasu, Ken (Journal of applied glycoscience : JAG, 2019)
Novel bioreactor beads for simultaneous saccharification and fermentation (SSF) of lime-pretreated rice straw (RS) into ethanol were prepared. Genetically modified Saccharomyces cerevisiae cells expressing genes encoding xylose reductase, xylitol dehydrogenase, and xylulokinase were immobilized in calcium alginate beads containing inorganic lightweight filler particles to reduce specific gravity. For SSF experiments, the beads were floated in slurry composed of lime-pretreated RS and enzymes and incubated under CO2 atmosphere to reduce the pH for saccharification and fermentation. Following this reaction, beads were readily picked up from the upper part of the slurry and were directly transferred to the next vessel with slurry. After 240 h of incubation, ethanol production by the beads was equivalent to that by free cells, a trend that was repeated in nine additional runs, with slightly improved ethanol yields. Slurry with pre-saccharified lime-pretreated RS was subjected to SSF with floating beads for 168 h. Although higher cell concentrations in beads resulted in more rapid initial ethanol production rates, with negligible diauxic behavior for glucose and xylose utilization, no improvement in the ethanol yield was observed. A fermentor-scale SSF experiment with floating beads was successfully performed twice, with repeated use of the beads, resulting in the production of 40.0 and 39.7 g/L ethanol. There was no decomposition of the beads during agitation at 60 rpm. Thus, this bioreactor enables reuse of yeast cells for efficient ethanol production by SSF of lignocellulosic feedstock, without the need for instruments for centrifugation or filtration of whole slurry.